Immunomodulation properties of biotics and food allergy in pediatrics - Burgos, Fernando (2022)
Preterm birth, C-section, antibiotic use, and limited breastfeeding are blamed in part for the increasing incidence of chronic noncommunicable diseases among children, such as allergies, mainly cow’s milk protein allergy (CMPA). Those who develop allergic diseases, against those who do not, show differences in the composition of their gut microbiota during the first months of life. Early interventions to modulate the intestinal microbiota and the immune system may be the key tools for the management of CMPA. Clinical judgment and the interdisciplinary work of allergists, gastroenterologists, immunologists, microbiologists, and nutritionists will allow pediatricians to achieve an adequate diagnosis and a timely treatment. In this setting, the use of biotics (prebiotics, probiotics, synbiotics, and postbiotics) as supplementary dietary tools is scientifically supported at present and seems to be very promising for the prevention and treatment of these conditions.